Methylation of replicating and post-replicated mouse L-cell DNA. - Gruenbaum, Y (1983)
We have introduced [alpha-32P]dGTP into permeabilized cells and measured the degree of methylation at CpG sites by nearest-neighbor analysis. This method reveals a lag of approximately 1 min between DNA synthesis and the modification event. When methylation is inhibited by the addition of S-adenosyl-L-homocysteine in the presence of continued DNA synthesis, the resulting hemimethylated sites are methylated immediately after the release of inhibition. The results suggest that the methylase activity in the cell allows immediate methylation but conditions at the replication fork bring about a short delay in the onset of the modification reaction.